Exploring the inter-relationships between leadership, management, and governance in enhancing performance in quintile 1 primary schools - Muller, Gregorius Daniel (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.